Cohort profile: the Hortega Study for the evaluation of non-traditional risk factors of cardiometabolic and other chronic diseases in a general population from Spain. Issue 6 (27th June 2019) - Tellez-Plaza, Maria; Briongos-Figuero, Laisa; Pichler, Gernot; Dominguez-Lucas, Alejandro; Simal-Blanco, Fernando; Mena-Martin, Francisco J; Bellido-Casado, Jesus; Arzua-Mouronte, Delfin; Chaves, Felipe Javier; Redon, Josep; Martin-Escudero, Juan Carlos
Abstract : Purpose: The Hortega Study is a prospective study, which investigates novel determinants of selected chronic conditions with an emphasis on cardiovascular health in a representative sample of a general population from Spain. Participants: In 1997, a mailed survey was sent to a random selection of public health system beneficiaries assigned to the University Hospital Rio Hortega's catchment area in Valladolid (Spain) (n=11 423, phase I), followed by a pilot examination in 1999–2000 of 495 phase I participants (phase II). In 2001–2003, the examination of 1502 individuals constituted the Hortega Study baseline examination visit (phase III, mean age 48.7 years, 49% men, 17% with obesity, 27% current smokers). Follow-up of phase III participants (also termed Hortega Follow-up Study) was obtained as of 30 November 2015 through review of health records (9.5% of participants without follow-up information). Findings to date: The Hortega Study integrates baseline information of traditional and non-traditional factors (metabolomic including lipidomic and oxidative stress metabolites, genetic variants and environmental factors, such as metals), with 14 years of follow-up for the assessment of mortality and incidence of chronic diseases. Preliminary analysis of time to event data shows that well-known cardiovascular risk factors are associated with cardiovascular incidence rates, which add robustness to our cohort. Future plans: In 2020, we will review updated health and mortality records of this ongoing cohort for a 5-year follow-up extension. We will also re-examine elder survivors to evaluate specific aspects of ageing and conduct geolocation to study additional environmental exposures. Stored biological specimens are available for analysis of new biomarkers. The Hortega Study will, thus, enable the identification of novel factors based on time to event data, potentially contributing to the prevention and control of chronic diseases in ageing populations.